2019
DOI: 10.1038/s41598-019-47578-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Validation of an Ex Vivo, Patient-Derived 3D Spheroid Model for Response Predictions in Newly Diagnosed Ovarian Cancer

Abstract: Although 70–80% of newly diagnosed ovarian cancer patients respond to first-line therapy, almost all relapse and five-year survival remains below 50%. One strategy to increase five-year survival is prolonging time to relapse by improving first-line therapy response. However, no biomarker today can accurately predict individual response to therapy. In this study, we present analytical and prospective clinical validation of a new test that utilizes primary patient tissue in 3D cell culture to make patient-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 43 publications
1
51
0
Order By: Relevance
“…The results obtained indicated that the breast cancer spheroid model was not only predictive but might also be selective in discerning ineffective from effective treatment options. 48 Shuford et al 49 using ULA plates for spheroids generation, developed and validated a 7 days test to make patient-specific response predictions prior to initiation of ovarian cancer treatment in the clinic. 49 In a study population of 44, Kamilla Swiech https://orcid.org/0000-0002-4811-9751…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained indicated that the breast cancer spheroid model was not only predictive but might also be selective in discerning ineffective from effective treatment options. 48 Shuford et al 49 using ULA plates for spheroids generation, developed and validated a 7 days test to make patient-specific response predictions prior to initiation of ovarian cancer treatment in the clinic. 49 In a study population of 44, Kamilla Swiech https://orcid.org/0000-0002-4811-9751…”
Section: Discussionmentioning
confidence: 99%
“…In a very recent study with ovarian cancer, spheroids from 92 patients were generated in 24 h and then treated for 72 h with first-and second-line therapies. By comparing patient clinical responses with the spheroid tests, the authors show an outstanding prediction efficiency of 89% [34]. However, despite being 3D, most spheroids lack the original architecture, as well as stromal and immune components, which are crucial modulators of drug response.…”
Section: Spheroidsmentioning
confidence: 99%
“…To generate patient-derived spheroids, tumor pieces of freshly collected tissues are dissociated (partially or completely) and then cultured either in low adhesion plates or embedded in matrigel [32][33][34][35]. In a very recent study with ovarian cancer, spheroids from 92 patients were generated in 24 h and then treated for 72 h with first-and second-line therapies.…”
Section: Spheroidsmentioning
confidence: 99%
“…Microfluidic platforms for tumor slices [ 20 , 21 , 22 , 23 ] and bioprinting technologies have also emerged [ 24 ], as have systems that model angiogenesis, metastasis, extravasation, and other phenomena [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. While these systems have shown utility in modeling chemotherapeutic responses and immune checkpoint behavior, most are non-perfused systems that do not capture the dynamics of lymphocyte migration and drug transport [ 34 ], and their study is often of limited duration due to a rapid decline in viability beyond 24–72 h [ 35 , 36 ]. An urgent need remains for engineered platforms capable of supporting viable tumor fragments over a longer time frame, accommodating dynamic interactions between lymphocytes and tumors, and enabling real-time imaging in order to quantify tumor killing and lymphocyte infiltration in response to ICI treatments.…”
Section: Introductionmentioning
confidence: 99%